PERANCANGAN APLIKASI DATABASE PENJUALAN PADA USAHA YULIWARDIS SNACK PADANG - Fatimah, Revi; Wira, Variyetmi; Gustati, Gustati (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
Small and Micro Enterprises (SME) are type of enterprises that can be carried out by the community to improve their welfare. The most in-demand enterprise of consumers is the food enterprise, one of which is Yuliwardi's Snack, which then chosen as the subject of this study. The challenge faced by enterprises is inconsistency of their sales records. This study aims to design a bookkeeping application that is needed by enterprises with an order-based sales system. The data were collected through semi-structured interview with the owner of this SME. Whereas the design analysis in this study was based on PIECES analysis in constructing a database design framework. The sales application was created using Microsoft Access 2013. The design of the sales application program consisted of calculating sales orders, recapitulating daily and monthly sales values, and generating receipts in any sales transaction. In view of this, the benefit obtained by the enterprises was the efficiency of recording monthly sales.